2017
DOI: 10.1107/s2414314617008999
|View full text |Cite
|
Sign up to set email alerts
|

4-Benzyl-6-bromo-2-(4-chlorophenyl)-4H-imidazo[4,5-b]pyridine

Abstract: In the title compound, C19H13BrClN3, the chlorophenyl ring occupies an equatorial position with respect to the mean plane of the imidazopyridine unit, while the other phenyl ring is twisted by 4.1 (2)° with respect to the mean plane of the imidazopyridine unit. In the crystal, pairwise C—H...Br interactions link the molecules into dimers, forming anR22(16) ring motif. In addition, weak π–π stacking interactions stabilize the crystal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…4-benzyl-6-bromo-2-phenyl-4H-imidazo[4,5-b]pyridine (Ouzidan et al, 2010b), 4-benzyl-6-bromo-2-methoxyphenyl-4H-imidazo-[4,5-b]pyridine monohydrate (Ouzidan et al, 2010a) and 4-benzyl-6-bromo-2-(4-chlorophenyl)-4H-imidazo[4,5-b]pyridine (Bourichi et al, 2017), have been also reported.…”
Section: Figurementioning
confidence: 99%
“…4-benzyl-6-bromo-2-phenyl-4H-imidazo[4,5-b]pyridine (Ouzidan et al, 2010b), 4-benzyl-6-bromo-2-methoxyphenyl-4H-imidazo-[4,5-b]pyridine monohydrate (Ouzidan et al, 2010a) and 4-benzyl-6-bromo-2-(4-chlorophenyl)-4H-imidazo[4,5-b]pyridine (Bourichi et al, 2017), have been also reported.…”
Section: Figurementioning
confidence: 99%
“…For example they are used as antiviral (Scribner et al 2007), antibacterial (Liang et al 2007 and anti-neuroinflammatory agents (Ock et al, 2010). As a continuation of our research on the development of substituted imidazo[4,5-b]pyridine derivatives (Bourichi et al, 2017), we report here the synthesis and structure of a new imidazo [4,5-b]pyridine derivative synthesized by the reaction of methyl iodide and 6-bromo-2-(4-methoxyphenyl)-3H-imidazopyridine in the presence of a catalytic quantity of tetra-n-butylammonium bromide under phase transfer catalysis conditions.…”
Section: Structure Descriptionmentioning
confidence: 99%